Globalism and capitalism international cooperation in protecting Indonesian workers from the threat of violence from other countries and negative impacts - Harahap, Riky Ovaliansyah (Privietlab, 2025)
Globalization has brought significant changes to Indonesia's labor dynamics, including increasing labor mobility abroad and the problem of low labor quality due to educational and employment access disparities. This research aims to explain Indonesia's policies for the protection of labor, as well as the forms of international cooperation carried out to protect Indonesian migrant workers. Using the concept of Labor Protection and the framework of International Labor Law (ILO), this study analyzes national regulations, migrant worker protection practices, and Indonesia's collaboration with international organizations (OIs). The results of the study show that the number of Indonesian migrant workers, which reaches around eight million, contributes greatly to the national economy but is still dominated by unskilled workers who are vulnerable to exploitation. The government has made protection efforts through Law No. 18 of 2017 and the policy of exemption of placement fees in certain sectors, although its implementation faces challenges in regional capacity and compliance with placement institutions. At the global level, cooperation through the Decent Work Country Programme (DWCP) between Indonesia and the ILO strengthens the protection of migrant workers through the development of fair industrial relations, expansion of social security, and improvement of the quality of decent work.